2013
DOI: 10.1097/dcr.0b013e3182812842
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Recovery After Surgery Programs Versus Traditional Care for Colorectal Surgery

Abstract: Enhanced recovery after surgery programs are safe and effective, and increased implementation is justified for perioperative care in colorectal surgery. Future studies may examine the benefits of enhanced recovery after surgery programs in elderly patients and in other GI surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
241
1
17

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 431 publications
(269 citation statements)
references
References 40 publications
10
241
1
17
Order By: Relevance
“…The ERP is a comprehensive perioperative CRS care pathway that has been shown to reduce postoperative morbidity and length of hospitalization. [9][10][11][12][13][14][15][16][17] Similarly, the SSIB is a perioperative care program that systematically provides evidence-supported measures for surgical wound infection prevention and has been shown to reduce the rate of postoperative wound infection. [18][19][20][21][22] Although both the ERP and SSIB have individually been shown to improve outcomes after CRS, the effect of their combined presence has not, to our knowledge, previously been reported in the literature.…”
mentioning
confidence: 99%
“…The ERP is a comprehensive perioperative CRS care pathway that has been shown to reduce postoperative morbidity and length of hospitalization. [9][10][11][12][13][14][15][16][17] Similarly, the SSIB is a perioperative care program that systematically provides evidence-supported measures for surgical wound infection prevention and has been shown to reduce the rate of postoperative wound infection. [18][19][20][21][22] Although both the ERP and SSIB have individually been shown to improve outcomes after CRS, the effect of their combined presence has not, to our knowledge, previously been reported in the literature.…”
mentioning
confidence: 99%
“…There is already substantial evidence in the literature demonstrating the effectiveness of adopting ERAS based protocols in elective surgery (6)(7)(8)(9)(10), resulting in a change in clinical practice and recommendations to use them in ES have already been made by Royal College of Surgeons, UK (11).…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analyses have confirmed that ERAS protocols in colorectal surgery positively impact on postoperative outcomes (4,5,(16)(17)(18). Despite this, a recent survey of New Zealand and Australian colorectal surgeons found that 55% of responders did not care for patients in a formalised ERAS pathway (3).…”
Section: Discussionmentioning
confidence: 99%